Development of Industrial Culture Learning Module to Improve Student's Soft Skill at SMK Muhammadiyah 2 Kuningan - Asyuyuti, Idar Badaruddin; Sudana, I Made; Kuswardinah, Asih (Universitas Negeri Semarang, 2022)
Learning activities are a system that is deliberately planned with the modification of various conditions that are directed so that the objectives contained in the curriculum can be achieved, in the implementation of the learning process in Vocational High Schools (SMK) there are many problems that arise from various factors supporting the learning process starting from students as students, teachers as educators, methods as a means of delivering the subject matter, learning support facilities and school policies that can affect the smoothness of the learning process. Selection of the right learning media can improve learning outcomes as well as the elaboration of new habits by developing soft skills of students themselves by using e-modules for class XII TKRO 4 and those who do not use e-module XII TBSM 2 at SMK Muhammadiyah 2 Kuningan for the academic year 2020/ 2021. The purpose of this research is to develop an E-Module on Industrial Culture Materials with a Problem Base Learning learning model to improve students' soft skills. This study uses research and development or R and D methods. The design chosen is ADDIE, which includes five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The research uses various instruments, namely (1) a feasibility assessment sheet for e-modules; (2) e-module practicality questionnaire; and (3) a questionnaire on the effectiveness of the e-module to measure the soft skills of class XII TKRO 4 and XII TBSM 2 students at SMK Muhammadiyah 2 Kuningan. The data analysis used is (1) categorical to determine the feasibility level of the e-module; (2) Guttman's categorization to determine the level of practicality of e-modules, using the coefficients Kr and Ks; and (3) N-Gain and different N-Gain tests using t-test, to determine the effectiveness of the e-module on student learning outcomes. Based on the feasibility test, practicality test, and the effectiveness test of the e-module, the industrial culture material developed, according to the responses of media experts and material experts, obtained the criteria for a very feasible e-module response. Responses from teachers and students as user responses to the practicality test of the e-module obtained very practical assessment criteria. And from the effectiveness test in the experimental class, the e-module obtained effective and significant criteria for improving the soft skills of class XII TKRO 4 and XII TBSM 2 students at SMK Muhammadiyah 2 Kuningan.